SAFETY ISSUES IN LIGHT AND CHEMICAL INDUSTRY TECHNOLOGY - NESTER, ANATOLIY; MITIUK, LIUDMYLA; POLUKAROV, YURI; PARSHENKO, KONSTANTIN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The war of the Russian state against independent Ukraine presented society with new complex tasks regarding the production of military ammunition and combat equipment, which is provided with the participation of the light and chemical industry. In the conditions of a shortage of military ammunition, the production of shells, missiles and mines for military operations by our army, ensuring the stable and productive work of these industries becomes a task that must be performed quickly and efficiently in order to replenish the Armed Forces of the state. In such difficult conditions, methods of broad involvement of the population, including those of retirement age and the disabled, should be used for the deployment of production in territories not captured by the enemy. The work is devoted to the improvement of occupational health and safety of the personnel of the light and chemical industry, the dissemination of knowledge about military operations and the efforts of the management of enterprises, districts and individuals to preserve health and work promotion in conditions of martial law. The efficiency of the light and chemical industry is determined by the quality and quantity of personnel who work and continue to perform their functions in this difficult time for the state. Most of the management personnel of these enterprises have a shortage of labor force and deliberately go to attract people of retirement age, disabled people, and students to work. Working with such personnel requires special attention from the employer, because the legislation provides for a number of requirements that should be followed. It is important to remember the selection of the company’s management team, who are able and able to work with this category of personnel, which requires the creation of conditions for productive work. Here, the psychological state, the possibility of creating an individual work schedule, and the creation of part-time employment opportunities (especially for student youth) are important. But working with such personnel in the conditions of martial law at enterprises of the light and chemical industry requires increased attention when carrying out labor protection measures, which require additional clarifications on behavior during air raids, detection of explosive substances and ammunition from weapons